Individual Leg and Joint Work during Sloped Walking for People with a Transtibial Amputation Using Passive and Powered Prostheses - Jeffers, Jana R.; Grabowski, Alena M. (Frontiers in Robotics and AI, 2017)
People with a transtibial amputation using passive-elastic prostheses exhibit reduced prosthetic ankle power and push-off work compared to non-amputees and compensate by increasing their affected leg (AL) hip joint work and unaffected leg (UL) ankle, knee, and hip joint and leg work during level-ground walking. Use of a powered ankle-foot prosthesis normalizes step-to-step transition work during level-ground walking over a range of speeds for people with a transtibial amputation, but the effects on joint work during level-ground, uphill and downhill walking have not been assessed. We investigated how use of passive-elastic and powered ankle-foot prostheses affect leg joint biomechanics during level-ground and sloped walking. 10 people with a unilateral transtibial amputation walked at 1.25 m/s on a dual-belt force-measuring treadmill at 0°, ±3°, ±6°, and ±9° using their own passive-elastic and a powered prosthesis (BiOM T2, BionX Medical Technologies, Inc. Bedford, MA, USA) while we measured kinematic and kinetic data. We calculated AL and UL prosthetic, ankle, knee, hip, and individual leg positive, negative, and net work. Use of a powered compared to passive-elastic ankle-foot prosthesis resulted in greater AL prosthetic and individual leg net work on uphill and downhill slopes. Over a stride, AL prosthetic positive work was 23-30% greater (p<0.05) during walking on uphill slopes of +6°, and +9°, prosthetic net work was up to 10 times greater (more positive) (p≤0.005) on all uphill and downhill slopes and individual leg net work was 146% and 82% more positive (p<0.05) at uphill slopes of +6° and +9°, respectively, with use of the powered compared to passive-elastic prosthesis. Greater prosthetic positive and net work through use of a powered ankle-foot prosthesis during uphill and downhill walking improves mechanical work symmetry between the legs, which could decrease metabolic cost and improve functional mobility in people with a transtibial amputation.